Decision-making for paired comparison using the extended amended Davidson model. Issue 4 (16th February 2017) - Altaf, Saima; Aslam, Muhammad; Liaqat, Madiha
ABSTRACT: For decision purpose, one of the commonly used statistical applications is the comparison of two or more objects or characteristics. Sometimes, it is not possible to compare the objects at a time or when the number of objects under study is large and the differences between the objects become small, then a useful way is to compare them in pairwise manner. Because of its practical nature, the fields in which paired comparison techniques are being used are numerous. Many Bayesian statisticians have focused their attention on the practical and usable paired comparison technique and have successfully performed the Bayesian study of many of the paired comparison models. In the current study, analysis of the amended Davidson model (ADM) which has been extended after incorporating the order effect parameter is narrated. For this intention, both the informative and non informative priors are used. The said model is studied for the case of four treatments which are compared pairwise.